On the Effects of Barriers to International Investment - Stulz, René M. (Journal of Finance, 1981)
A simple model is presented in which it is costly for domestic investors to hold foreign assets. The implications of the model for the composition of optimal portfolios at home and abroad are derived. It is shown that all foreign assets with a beta larger than some beta β * plot on either one of two security market lines. Some foreign assets with a beta smaller than β * are not held by domestic investors even if their expected return is increased slightly.